Disabled Workers Outperform Non-Disabled Peers in Indonesia: “Pekerja Disabilitas Mengungguli Rekan Kerja Non-Disabilitas di Indonesia” - Hadi Praseno; Kumara Adji Kusuma; Rifdah Abadiyah; Hasan Ubaidillah (Academia Open, 2024)
This study examines the productivity differences between disabled and non-disabled workers at PT. United Pharmatic Indonesia. Using a quantitative approach, data were collected from 120 employees in the production department through proportional random sampling and analyzed with SPSS 22. Questionnaires provided quantitative data on employee productivity. Results show no significant difference in productivity levels, with disabled workers having a slightly higher average score (39.59) than non-disabled workers (39.16). The findings suggest that disability does not negatively impact productivity, supporting inclusive hiring practices. Highlight: No significant productivity difference: Disabled and non-disabled workers show comparable productivity levels. Higher productivity in disabled workers: Slightly higher average productivity for disabled workers. Support for inclusive hiring: Findings encourage integrating disabled individuals into the workforce. Keywoard: worker productivity, disabilities, non-disabilities, quantitative research, SPSS